Programming Languages and Systems: 33rd European Symposium on Programming, ESOP 2024, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2024, Luxembourg City, Luxembourg, April 6–11, 2024, Proceedings, Part II - Weirich, Stephanie (Lecture Notes in Computer Science, 2024)
The two-volume open access book set LNCS 14576 + 14577 constitutes the proceedings of the 33rd European Symposium on Programming, ESOP 2024, which was held during April 6-11, 2024, in Luxemburg, as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2024. The 25 full papers and 1 fresh perspective paper presented in these proceedings were carefully reviewed and selected from 72 submissions. The papers were organized in topical sections as follows: Part I: Effects and modal types; bidirectional typing and session types; dependent types; Part II: Quantum programming and domain-specific languages; verification; program analysis; abstract interpretation.